Unraveling Morphology and Phase Control of NaLnF4 Upconverting Nanocrystals - Ren, J.; Jia, Guohua; Guo, Y.; Wang, A.; Xu, S. (American Chemical Society, 2016)
© 2015 American Chemical Society. Near-infrared to visible upconversion NaLnF4 (Ln = Pr to Lu and Y) nanocrystals hold great promise for use in biological labeling and imaging due to their intrinsic characteristics such as high chemical stability, nonblinking and sharp bandwidth luminescence, large Stokes shift, as well as appropriate and abundant energy states necessary for efficient energy transfer to achieve near-infrared to visible upconversion emission. However, there are still significant hurdles in the control of size, shape, and phase of NaLnF4 nanocrystals due to limited understanding of their growth behavior and growth mechanism. Here we describe an approach to facilely control the shape and phase of upconversion NaLnF4 nanocrystals. Besides the optimization of synthetic conditions such as organic surfactant and reaction temperature, we have developed a program, in which a correlation between the ionic radius of lanthanide ions and the shape/phase of NaLnF4 nanocrystals is established, to precisely control the shape and phase of NaLnF4 nanocrystals by precisely tuning the mean ionic radius of lanthanide ions through lanthanide doping. The availability of such upconverting nanocrystals with controlled size, shape, and phase provides a platform for applications ranging from biological imaging, biological sensing, and three-dimensional displays.